Method for detecting content of silicon element in enhanced nitrogen fixation core-spun yarn
Through a detection method including pretreatment, low-temperature calcination, melting and precipitation treatment, the problem of inaccurate analysis of the silicon element content in the enhanced nitrogen-encapsulated wire is solved, and timely and accurate detection of the silicon element content is achieved, providing important production guarantees for the metallurgical industry.
Patent Information
- Application Number
- CN202510027362.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art cannot accurately analyze the content of silicon elements in the enhanced nitrogen-fixed core wire, because the properties of the material are relatively stable and difficult to react with commonly used acidic solvents, resulting in the content of silicon elements that cannot be reported in time, affecting the production progress.
A detection method is adopted, including pretreatment, low-temperature calcination, melting, generation of potassium fluorosilicate and precipitation aging. The silicon element is converted into silica by low-temperature calcination, and potassium hydroxide is added as a flux at high temperature to generate fluorosilicate precipitate, and the silicon content is determined by acid-base titration.
This method can accurately and timely analyze the content of silicon elements in the reinforced nitrogen-fixed core wire, and is suitable for quantitative analysis of silicon elements of 20%-60%, providing production guarantees and is of great significance to the metallurgical industry.
Smart Images

Figure CN119804431A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical analysis, and specifically relates to a method for detecting the silicon content in a reinforced nitrogen-fixing cored wire. Background Art
[0002] Strengthened nitrogen-fixing cored wire is a new type of alloy raw material. Its main components are silicon nitride, manganese nitride and some silicon-containing impurities, which play a role in nitrogen fixation in steelmaking. The use of strengthened nitrogen-fixing cored wire can greatly reduce the consumption of precious metals such as vanadium nitrogen alloys, saving production costs. In the metallurgical industry, nitrogen can significantly improve the strength and hardness of steel. Nitrides not only have high hardness, but also have good corrosion resistance, which can improve the resistance of the steel surface and increase its service life in harsh environments. The silicon content in the strengthened nitrogen-fixing cored wire directly affects the nitrogen fixation effect. Therefore, timely and accurate analysis of the silicon content in the strengthened nitrogen-fixing cored wire is of great significance for production.
[0003] The conventional method of analyzing silicon is to use hydrofluoric acid-nitric acid to dissolve the sample. However, if this method is used to analyze the silicon content in the reinforced nitrogen-fixed cored wire, the result is seriously inconsistent with the actual content. Because the reinforced nitrogen-fixed cored wire is similar to the rare earth nitrogen alloy, it contains nitrogen, rare earth, manganese and other components, and its properties are relatively stable. It is not easy to react with nitric acid and hydrofluoric acid. Directly adding alkali, peroxide or nitrate cannot complete the decomposition, which leads to the inability to report the silicon content in time, which greatly affects the production progress. Summary of the invention
[0004] The purpose of the present invention is to provide a method for detecting the silicon content in the reinforced nitrogen-fixing cored wire in view of the problem that the reinforced nitrogen-fixing cored wire has a relatively stable property and is not easy to react with nitric acid and hydrofluoric acid, thereby causing the existing conventional method for analyzing the silicon content to be unsuitable for the reinforced nitrogen-fixing cored wire. The method can timely and accurately analyze the silicon content in the reinforced nitrogen-fixing cored wire, thus providing a guarantee for production and having important significance for the metallurgical industry.
[0005] The method for detecting the silicon content in the enhanced nitrogen-fixing cored wire of the present invention is suitable for quantitative analysis of silicon content of 20%-60%, and has a wide range of analysis. The specific technical scheme is as follows:
[0006] A method for detecting the silicon content in a nitrogen-fixing cored wire comprises the following steps:
[0007] (1) Pretreatment: First, peel off the outer layer of the enhanced nitrogen-fixing cored wire; then grind the core and mix it evenly to obtain a sample, and keep the sample dry. The enhanced nitrogen-fixing cored wire consists of a core and an outer layer, in which the core is the effective component, so the enhanced nitrogen-fixing cored wire to be tested needs to be pretreated.
[0008] (2) Low-temperature calcination: The sample obtained in step (1) is placed in a nickel crucible and calcined in a muffle furnace at 625-650° C. for 15-20 min; at the same time, at least two standard samples with known component contents are calcined at low temperature under the same conditions.
[0009] The present invention has found that if the temperature of low-temperature calcination of the sample is too low, the efficiency is low and the effect is poor, while if the temperature is too high, it will cause agglomeration. Therefore, the low-temperature range of calcination needs to be strictly controlled. In addition, the method of the present invention adopts a method of analyzing a standard sample with a known component content together with the sample to be tested. At least two standard samples are analyzed simultaneously with the sample. And the content range covered by the high and low standards of the standard sample needs to include the content value in the sample.
[0010] Step (2) The sample is placed in a nickel crucible for low-temperature calcination to convert the silicon element in the reinforced nitrogen-fixing cored wire into silicon dioxide, and to convert a small amount of silicon nitride into silicon dioxide, and to oxidize part of the sulfide to volatilize it, thereby reducing the intensity of subsequent reactions, preventing splashing caused by excessive local concentration, and increasing melting efficiency. The specific reaction is as follows:
[0011]
[0012] (3) Melting: After low-temperature calcination, take out the sample and cool it, add 1.9-2.1g potassium hydroxide, and then continue to burn at 625℃-650℃ for 18-20min. During this period, the direction of the crucible stand can be changed once to ensure uniform heating. The standard sample is melted under the same conditions.
[0013] In step (3), potassium hydroxide is used as a flux, and its reaction is relatively mild compared to peroxide. Potassium hydroxide provides potassium ions, paving the way for the subsequent reaction of generating potassium fluorosilicate, effectively avoiding the introduction of impurity ions. Potassium hydroxide is selected to react with the silicon dioxide and remaining silicon nitride generated in the low-temperature calcination in step (2) at a high temperature as follows:
[0014]
[0015] (4) Generating potassium fluorosilicate: After the melting is completed, the melt is taken out and cooled; the melt is leached with boiling water; about 70 mL of boiling water can be used to leach the melt in a 250 mL beaker. Then a mixed acid is used to dissolve to obtain a solution, and potassium chloride solid is added to the solution until saturation to generate potassium fluorosilicate precipitate; wherein the mixed acid is composed of 7.9-8.1 mL of hydrochloric acid with a mass fraction of 37%, 9.9-10.1 mL of nitric acid with a mass fraction of 65%, and 4.9-5.1 mL of hydrofluoric acid with a mass fraction of 40%. The standard sample is operated in the same manner to generate potassium fluorosilicate precipitate. Due to different ambient temperatures, the amount of potassium chloride added is adjusted according to the actual situation until saturation (i.e., the solid no longer dissolves).
[0016] After the sample is melted and cooled, it is leached with boiling water to convert the potassium silicate solid into an ionic state. Potassium fluorosilicate precipitation is generated under strong acid conditions. If the acidity is too low, it is easy to form co-precipitation of other salt fluorides and potassium fluorosilicate, which interferes with the determination. Therefore, hydrochloric acid is used to dissolve the salts, and nitric acid and hydrofluoric acid are used to provide acidity. Nitric acid can prevent the sample from precipitating silica gel and eliminate the interference of aluminum and titanium elements. Hydrofluoric acid provides fluoride ions to form potassium fluorosilicate precipitation.
[0017] Due to the common ion effect, a slightly excessive amount of precipitant is beneficial to the formation of precipitation. Therefore, adding the precipitant potassium chloride solid to saturate the solution is beneficial to the formation of potassium fluorosilicate.
[0018] In an acidic solution, silicon exists in the form of silicic acid. When hydrofluoric acid and a slightly excess amount of potassium chloride are added, the following reaction occurs to form potassium fluorosilicate precipitate:
[0019]
[0020] (5) Precipitation aging, filtration, and washing: Place the solution with saturated potassium chloride solid in cold water for 15-20 minutes to completely precipitate the potassium fluorosilicate. Then filter using filter paper and a plastic funnel; use an ethanol solution of potassium chloride as a washing liquid to wash the beaker and the precipitate 3-4 times each to avoid interference from iron ions and the like in the titration. The standard sample is operated in the same manner. However, excessive washing times will cause the potassium ion concentration in the system to be too high, affecting the decomposition of the potassium fluorosilicate precipitate, affecting the titration, and causing the result to be low.
[0021] The reaction to generate potassium fluorosilicate precipitate is a reversible reaction, and its reverse reaction is an endothermic reaction. Therefore, the low-temperature aging process in cold water is conducive to the formation of crystalline precipitate and can prevent the precipitate from hydrolyzing. In addition, in order to inhibit the reverse reaction, the common ion effect is utilized and potassium chloride solution is used during washing.
[0022] (6) Titration: transfer the precipitate obtained in step (5) together with the filter paper into a beaker, add 10% by mass potassium chloride protective solution, and crush the filter paper;
[0023] Add 6-10 drops of indicator and add sodium hydroxide standard solution until the indicator changes color;
[0024] Add neutral boiling water, add 2 drops of indicator, and titrate with sodium hydroxide standard solution under stirring until the indicator changes color and does not fade. The standard sample is titrated in the same way.
[0025] Because step (5) is to avoid precipitation decomposition, only washing 3-4 times, although most of the acid and iron ions are washed away after washing, the free acid in the precipitation after operation is not cleaned up, and there is still residual acid. And titration is acid-base titration, so it is necessary to ensure that the pH value of the system is neutral or at the indicator discoloration before the titration reaction. Therefore, after the filter paper with precipitation after filtration is crushed, an indicator is added, and sodium hydroxide is used to adjust the pH value until the indicator discolors. This process will produce certain systematic errors, but the present invention simultaneously adopts the method of calculating the average titer of high and low standard samples to eliminate systematic errors.
[0026] After adjusting the pH, add an appropriate amount of hot water above 90°C into the system. The precipitate reacts with water to release hydrofluoric acid. This reaction is the reverse reaction of the above precipitation process:
[0027]
[0028] Finally, the high and low standards and the sample are titrated with sodium hydroxide solution to complete the determination. The dissociation constants of silicic acid and hydrofluoric acid are quite different. The Ka of hydrofluoric acid is 7.2×10 -4 , the dissociation constant of silicic acid Ka'=2×10 -10 Therefore, during titration, sodium hydroxide first reacts with hydrofluoric acid, and the endpoint pH is in the range of 7.5-8.3. In this process, since standard samples are used simultaneously, there is no need to prepare a sodium hydroxide standard solution with a precise concentration, as long as the concentration of the solution before and after is consistent. The process has the following reactions:
[0029] HF+NaOH==NaF+H2O.
[0030] (7) Calculate silicon content:
[0031] First, based on the titration results of the standard sample of the synchronous analysis operation with the sodium hydroxide standard solution, the titration degree T (g / mL) of the sodium hydroxide standard solution with respect to silicon is calculated on average:
[0032] T=ω 标 ×m 标 / V 标 ;
[0033] In the formula, ω 标 ——The percentage of silicon in the standard sample (%);
[0034] m 标 ——Weigh the mass of the standard sample (g);
[0035] V 标 ——The volume of sodium hydroxide standard solution consumed by the standard sample (mL);
[0036] Then, according to the titer T calculated by the above formula, the silicon content is calculated according to the following formula:
[0037] Si (%) = (T × V / m) × 100%
[0038] Where, T is the titration of silicon by sodium hydroxide standard solution (g / mL);
[0039] V——The volume of sodium hydroxide standard solution consumed by sample titration (mL);
[0040] m——sample mass (g).
[0041] In the present invention, in step (1) of the method for detecting the silicon content in the enhanced nitrogen-fixing cored wire, the wire core is ground to 190-200 meshes.
[0042] In the present invention, in step (2) of the method for detecting silicon content in the reinforced nitrogen-fixing cored wire, 3-4 drops of ethanol are added to the sample after low-temperature calcination. The sample is prone to agglomeration after low-temperature calcination, and 3-4 drops of ethanol can be added as a dispersant if necessary. Studies have found that the amount of ethanol added is preferably 3-4 drops, and excessive amounts will reduce the effect after low-temperature calcination.
[0043] In the present invention, in step (5) of the method for detecting the silicon content in the enhanced nitrogen-fixing cored wire, the temperature of the cold water is 5-15°C.
[0044] In the present invention, the ethanol solution of potassium chloride in step (5) of the method for detecting the silicon content in the enhanced nitrogen-fixing cored wire is prepared by preparing 400 mL of potassium chloride with a mass fraction of 10% and 100 mL of anhydrous ethanol.
[0045] In the present invention, in step (5) of the method for detecting the silicon content in the enhanced nitrogen-fixing cored wire, the filter paper is a rapid filter paper.
[0046] In the present invention, in step (6) of the method for detecting the silicon content in the enhanced nitrogen-fixing cored wire, the indicator is selected from bromothymol blue or a mixed indicator of phenol blue + phenol red. The selection of bromothymol blue or phenol blue + phenol red, whose color change point is 7.5, or other indicators that change color in this atmosphere, can make the chemical measurement point and the mutation point closer, and reduce the system error.
[0047] In the present invention, the temperature of the neutral boiling water in step (6) of the method for detecting the silicon content in the enhanced nitrogen-fixing cored wire is ≥90°C.
[0048] The beneficial effects of the present invention are as follows: the method for detecting the silicon content in the enhanced nitrogen-fixing cored wire of the present invention is suitable for the quantitative analysis of the silicon element in alloys with complex chemical compositions and poorly soluble in hydrofluoric acid at room temperature, and can also be suitable for the quantitative analysis of the silicon element in general alloys. The method can timely and accurately analyze the silicon content in the enhanced nitrogen-fixing cored wire, thus providing a guarantee for production and having important significance for the metallurgical industry.
[0049] The detection method is based on traditional acid-base titration, which has low analysis cost, short analysis time, strong test operability, easy acquisition of reagents, and is suitable for routine factory inspection.
[0050] In addition, the present invention adopts the principle of high and low standards, and uses standard samples instead of blank tests to eliminate the systematic error of the test. Both the calculation process and the test process are relatively simple.
[0051] Compared with the national standard requirements for silicon alloys, this method has good accuracy, repeatability and precision. The difference in analysis results of the same sample by the same analyst under the same conditions is ≤0.19; the difference between the analysis result and the standard value is ≤0.23. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 The present invention provides a flow chart of the method for detecting the silicon content in the enhanced nitrogen-fixing cored wire.
[0053] Figure 2 This is the bias mean plot of directly adding flux in Experimental Example 2. DETAILED DESCRIPTION
[0054] The technical solution of the present invention is described in detail below.
[0055] Example 1
[0056] The method for detecting the silicon content in the enhanced nitrogen-fixing cored wire comprises the following steps:
[0057] (1) Pretreatment: First, the outer coating of the reinforced nitrogen-fixing cored wire is peeled off; then, the wire core is ground to 200 mesh and mixed evenly to obtain a sample, and the sample is kept dry.
[0058] (2) Low-temperature calcination: The sample obtained in step (1) was placed in a nickel crucible and calcined in a muffle furnace at 625° C. for 15 min. At the same time, two standard samples with known component contents were calcined at low temperature under the same conditions.
[0059] (3) Melting: After low-temperature calcination, the sample was taken out and cooled, 2.0 g of potassium hydroxide was added, and then calcined at 625° C. for 20 min. The standard sample was melted under the same conditions.
[0060] (4) Forming potassium fluorosilicate: After the melting is completed, the melt is taken out and cooled; the melt is leached into a 250 mL beaker with 70 mL boiling water.
[0061] Then, a mixed acid was used for dissolution to obtain a solution, the volume of the solution was controlled at 120 mL, and 6 g of potassium chloride solid was added to the solution to generate potassium fluorosilicate precipitate.
[0062] The mixed acid consists of 8.0 mL of hydrochloric acid with a mass fraction of 37%, 10.0 mL of nitric acid with a mass fraction of 65%, and 5.0 mL of hydrofluoric acid with a mass fraction of 40%.
[0063] The standard sample is subjected to the same operation to generate potassium fluorosilicate precipitate;
[0064] (5) Precipitation aging, filtration, and washing: The solution to which saturated potassium chloride solid was added in step (4) was placed in cold water at 5° C. for 15 min to completely precipitate the potassium fluorosilicate.
[0065] Then filter with fast filter paper and funnel; after filtering, use ethanol solution of potassium chloride as washing liquid to wash the beaker and precipitate three times respectively. The ethanol solution of potassium chloride is prepared by 400 mL of 10% potassium chloride by mass and 100 mL of anhydrous ethanol.
[0066] The standard samples were subjected to the same operation.
[0067] (6) Titration: The precipitate obtained in step (5) together with the filter paper was transferred into a 250 mL beaker, 15 mL of 10% potassium chloride protective solution was added, and the filter paper was crushed.
[0068] Add 6-10 drops of bromothymol blue indicator and add sodium hydroxide standard solution until the color turns blue.
[0069] Add 150 mL of neutral boiling water and 2 drops of bromothymol blue indicator, and titrate with standard sodium hydroxide solution under stirring until the blue color does not fade.
[0070] The standard samples are processed in the same manner;
[0071] (7) Calculate silicon content:
[0072] First, based on the titration results of the standard sample of the synchronous analysis operation with the sodium hydroxide standard solution, the average titration degree T of the sodium hydroxide standard solution with respect to silicon is calculated, g / mL:
[0073] T=ω 标 ×m 标 / V 标 ;
[0074] In the formula, ω 标 ——The percentage of silicon in the standard sample, %;
[0075] m 标 ——Weigh the mass of the standard sample, g;
[0076] V 标 ——The volume of sodium hydroxide standard solution consumed by the standard sample, mL;
[0077] Then, based on the calculated titer T, the silicon content is calculated according to the following formula:
[0078] Si(%)=(T×V / m)×100%;
[0079] Where, T is the titration degree of silicon by sodium hydroxide standard solution, g / mL;
[0080] V——The volume of sodium hydroxide standard solution consumed in sample titration, mL;
[0081] m——sample mass, g.
[0082] Experimental Example 1
[0083] 1. Experimental purpose: To investigate the effect of the amount of hydrofluoric acid in the mixed acid on the test results.
[0084] 2. Experimental methods:
[0085] The operation was carried out according to the method and steps described in Example 1, and the following mixed acids were used as experimental reagents.
[0086] Mixed acid 1#: 8.0 mL of hydrochloric acid with a mass fraction of 37% + 10.0 mL of nitric acid with a mass fraction of 65% + 2.0 mL of hydrofluoric acid with a mass fraction of 40%.
[0087] Mixed acid 2#: 8.0 mL of hydrochloric acid with a mass fraction of 37% + 10.0 mL of nitric acid with a mass fraction of 65% + 5.0 mL of hydrofluoric acid with a mass fraction of 40%.
[0088] Mixed acid 3#: 8.0 mL of hydrochloric acid with a mass fraction of 37% + 10.0 mL of nitric acid with a mass fraction of 65% + 10.0 mL of hydrofluoric acid with a mass fraction of 40%.
[0089] Six groups of experiments were conducted for each mixed acid.
[0090] 3. Experimental Results
[0091] The experimental results are shown in Table 1.
[0092] Table 1
[0093]
[0094] Experimental Example 2
[0095] 1. Experimental purpose: In the existing technology, flux is usually added in advance and melted synchronously with the sample.
[0096] The effects of low-temperature calcination followed by addition of flux in the present invention and direct addition of flux in the prior art on the test results are compared.
[0097] 2. Experimental methods:
[0098] The operation of adding flux directly: first add 2.0g potassium hydroxide into a nickel crucible, then add the pretreated sample, and calcine in a muffle furnace at 625℃ for 20min.
[0099] The rest is the same as in Example 1.
[0100] 3. Experimental Results
[0101] The experimental results are shown in Table 2 and Figure 2 .
[0102] Table 2
[0103] Experiment No. The present invention Directly add flux Standard value Bias of the present invention Direct flux addition bias 1 53.63 53.35 53.73 -0.1 -0.38 2 53.75 53.43 53.73 -0.02 -0.3 3 44.28 44.11 44.32 -0.04 -0.21 4 44.35 44.19 44.32 0.03 -0.25 5 23.83 23.61 23.72 0.1 -0.11 6 23.67 23.62 23.72 -0.05 -0.1
[0104] Combining Table 2 and Figure 2 It can be seen that directly adding flux for melting has a larger error than the method of the present invention, and the bias has a certain linearity.
[0105] Experimental Example 3
[0106] 1. Experimental purpose: To verify the accuracy and precision of the method described in this invention.
[0107] 2. Experimental Results
[0108] The experimental results are shown in Table 3.
[0109] Table 3
[0110]
[0111] It can be seen from the data in Table 3 that, using the detection method of the present invention, the difference in analysis results of the same sample by the same laboratory technician under the same conditions (repeatability) does not exceed 0.19; the difference in analysis results of the same sample by different laboratory technicians (reproducibility) does not exceed 0.29; the difference between the laboratory technician's analysis result and the standard value (accuracy) does not exceed 0.23.
Claims
1. A method for detecting the silicon content in a nitrogen-fixing cored wire, characterized in that: The following steps are involved: (1) Pretreatment: First, the outer coating of the reinforced nitrogen-fixing cored wire is peeled off; then, the wire core is ground and mixed evenly to obtain a sample, and the sample is kept dry; (2) low-temperature calcination: placing the sample obtained in step (1) in a nickel crucible and calcining in a muffle furnace at 625-650° C. for 15-20 min; at the same time, at least two standard samples with known component contents are calcined at low temperatures under the same conditions; (3) Melting: After low-temperature calcination, the sample is taken out and cooled, 1.9-2.1 g of potassium hydroxide is added, and then calcined at 625°C-650°C for 18-20 min; the standard sample is melted under the same conditions; (4) Generating potassium fluorosilicate: After the melting is completed, the melt is taken out and cooled; the melt is leached with boiling water; then a mixed acid is used to dissolve the melt to obtain a solution, and potassium chloride solid is added to the solution until saturated to generate potassium fluorosilicate precipitate; wherein the mixed acid is composed of 7.9-8.1 mL of hydrochloric acid with a mass fraction of 37%, 9.9-10.1 mL of nitric acid with a mass fraction of 65%, and 4.9-5.1 mL of hydrofluoric acid with a mass fraction of 40%; the standard sample is subjected to the same operation to generate potassium fluorosilicate precipitate; (5) Precipitation aging, filtration, and washing: The solution to which saturated potassium chloride solid was added in step (4) was placed in cold water for 15-20 min; Then filter using filter paper and funnel; After filtering, the precipitate is washed with an ethanol solution of potassium chloride as a washing liquid; The standard samples are processed in the same manner; (6) Titration: transfer the precipitate obtained in step (5) together with the filter paper into a beaker, add 10% by mass potassium chloride protective solution, and crush the filter paper; Add 6-10 drops of indicator and add sodium hydroxide standard solution until the indicator changes color; Add neutral boiling water, add 2 drops of indicator, and titrate with sodium hydroxide standard solution under stirring until the indicator changes color without fading; The standard samples are processed in the same manner; (7) Calculate silicon content: First, based on the titration results of the standard sample of the synchronous analysis operation with the sodium hydroxide standard solution, the average titration degree T of the sodium hydroxide standard solution with respect to silicon is calculated, g / mL: T=ω 标 ×m 标 / V 标 ; In the formula, ω 标 ——The percentage of silicon in the standard sample, %; m 标 ——Weigh the mass of the standard sample, g; V 标 ——The volume of sodium hydroxide standard solution consumed by the standard sample, mL; Then, based on the calculated titer T, the silicon content is calculated according to the following formula: Si(%)=(T×V / m)×100%; Where, T is the titration degree of silicon by sodium hydroxide standard solution, g / mL; V——The volume of sodium hydroxide standard solution consumed by sample titration, mL; m——sample mass, g.
2. The method for detecting the silicon content in the enhanced nitrogen-fixing cored wire according to claim 1, characterized in that: In the step (1), the wire core is ground to 190-200 mesh.
3. The method for detecting the silicon content in the enhanced nitrogen-fixing cored wire according to claim 1, characterized in that: In the step (2), after low-temperature calcination, 3-4 drops of ethanol are added to the sample.
4. The method for detecting the silicon content in the enhanced nitrogen-fixing cored wire according to claim 1, characterized in that: The temperature of the cold water in step (5) is 5-15°C.
5. The method for detecting the silicon content in the enhanced nitrogen fixing cored wire according to claim 1, characterized in that: The ethanol solution of potassium chloride in step (5) is prepared by 400 mL of potassium chloride with a mass fraction of 10% and 100 mL of anhydrous ethanol.
6. The method for detecting the silicon content in the enhanced nitrogen-fixing cored wire according to claim 1, characterized in that: In the step (5), the filter paper is quick filter paper.
7. The method for detecting the silicon content in the enhanced nitrogen fixing cored wire according to claim 1, characterized in that: In the step (5), the precipitate is washed 3-4 times.
8. The method for detecting the silicon content in the enhanced nitrogen-fixing cored wire according to claim 1, characterized in that: In the step (6), the indicator is bromothymol blue or a mixed indicator of phenol blue and phenol red.
9. The method for detecting the silicon content in the enhanced nitrogen-fixing cored wire according to claim 1, characterized in that: The temperature of the neutral boiling water in step (6) is ≥90°C.
Citation Information
Patent Citations
Method for rapidly and accurately detecting content of silicon in nitrification intensifier
CN104502217A
Method for detecting silicon dioxide in silica sand through potassium fluosilicate volumetric method
CN105588833A
Method for determining content of silica in phosphorus rock by potassium fluosilicate volumetric technology
CN107655886A
Analysis method for determining Si and Ti components in titanium nitride cored wire
CN114414555A